The Association Between Changes in Plasma Short-Chain Fatty Acid Concentrations and Hypertension in Children With Chronic Kidney Disease - Lu, Pei-Chen; Hsu, Chien-Ning; Lin, I-Chun; Lo, Mao-Hung; Yang, Ming-Yu; Tain, You-Lin (Frontiers in Pediatrics, 2021)
Background: In children with chronic kidney disease (CKD), some children develop hypertension faster than others. One of the reasons may relate to endothelial dysfunction. Short-chain fatty acids (SCFAs), i.e., acetate, butyrate, and propionate, are known for reducing cardiovascular risks via preserving endothelial function. This study aimed to investigate the association between changes in plasma SCFA concentrations, and in cardiovascular and endothelial parameters in children with CKD. Methods: 105 children and adolescents meeting the criteria of CKD were enrolled in this study, and 65 subjects older than 6 were divided into two group based on the ambulatory BP measurements. The parameters of plasma SCFAs, endothelial function and morphology, and echocardiography were examed at the index visit and followed up after one year. Results: 27.69% of 65 subjects developed hypertension during this period. Plasma acetate increased by 22.75 µM in stable group (P < 0.001), while no statistical change was observed in worsened BP group. The index higher plasma butyrate was positively correlated with worsened BP (adjusted odd ratio, 1.381; P = 0.013). At the follow-up, plasma butyrate decreased by 2.12 µM and 4.41 µM in stable and worsened BP groups, respectively (P< 0.001). In 105 subjects, higher index plasma propionate was positively correlated with decreasing ejection fraction (adjusted odd ratio, 1.281; P = 0.046). Conclusions: We observed plasma acetate seems to have a role in preventing from hypertension in children with CKD. However, the index plasma propionate and butyrate seem to imply the development of cardiovascular problems in our one-year observation.